Cyclosporine Monotherapy in Pediatric Patients With Non-severe Aplastic Anemia: A Retrospective Analysis - Li, Hongmin; Fu, Lingling; Yang, Bixi; Chen, Hui; Ma, Jie; Wu, Runhui (Frontiers in Medicine, 2022)
Objective The management of children with non-severe aplastic anemia (NSAA) is undefined and the efficacies and benefits of immunosuppressive therapy remain inconsistent. The study aimed to investigate the efficacy of Cyclosporine (CsA) monotherapy for pediatric NSAA. Methods Clinical data of children with NSAA who had been treated with CsA monotherapy at the outpatient department of Beijing Children's Hospital, Capital Medical University, National Children's Medical Center from January 2017 to March 2021 was collected retrospectively. Patients who had been treated <1 years until the end of follow-up were excluded. Transfusion-independent NSAA was further divided into moderate NSAA and mild NSAA according to the degree of cytopenia. Progression was defined as the development of transfusion-dependent AA or SAA and relapse was considered when treatment failed after initial response. Results A total of 95 pediatric patients with NSAA were enrolled in this study with 49 (51.6%) patients confirmed as mild NSAA, 38 (40%) as moderate NSAA and 8 (8.4%) as transfusion-dependent NSAA. The median treatment time of CsA was 22 (12–44) months. The overall response rate (ORR) was 57.9%, with 30.5% CR and 27.4% PR. Unexpectedly, patients with mild NSAA acquired lowest ORR (46.9%), then patients with moderate NSAA (63.2%), while 8 patients who were transfusion-dependent all had an active response to CsA. The granulocyte and megakaryocyte response was 46.9 and 55.8% respectively, while the erythrocyte response rate was as low as 22.5%. Univariate analyses revealed that patients with lower platelet count and higher interleukin 10 level predict an active response to CsA while higher level of fetal hemoglobin (HbF) tended to be a negative factor. Data of Treg cells before and after 1 year's treatment was available in a total number of 40 patients. Paired comparison found that the percentage of Treg cells in CD4+ T cells was decreased after 1 year's treatment of CsA (6.78 ± 2.72 vs. 5.23 ± 2.06, P = 0.001),both in responders and non-responders. The degree of decline in Treg cells between two distinctive response groups had no significant difference (P>0.05). With a median follow-up time of 22 months, 10.9% of responders relapsed and maintained NSAA while 27.5% of non-responders progressed to SAA or became transfusion-dependent. The overall progression rate was 11.6%. Conclusion CsA monotherapy had heterogeneous effects in the treatment of children NSAA Treatment approaches should be hierarchical and individual in clinical. Patients with lower platelet count and higher interleukin 10 level predicted an active response to CsA. While higher level of fetal hemoglobin (HbF) tended to be a negative factor. The percentage of Treg cells in CD4+ T cells was decreased broadly after treatment.